2019
DOI: 10.1111/gcb.14895
|View full text |Cite
|
Sign up to set email alerts
|

Stream metabolism controls diel patterns and evasion of CO2 in Arctic streams

Abstract: Streams play an important role in the global carbon (C) cycle, accounting for a large portion of CO2 evaded from inland waters despite their small areal coverage. However, the relative importance of different terrestrial and aquatic processes driving CO2 production and evasion from streams remains poorly understood. In this study, we measured O2 and CO2 continuously in streams draining tundra‐dominated catchments in northern Sweden, during the summers of 2015 and 2016. From this, we estimated daily metabolic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
56
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 62 publications
(144 reference statements)
10
56
1
Order By: Relevance
“…In line with findings from similar studies from other environments (arctic tundra, boreal forest, temperate peatlands, alpine) (e.g. Rocher-Ros et al 2019;Riml et al 2019;Crawford et al 2017;Peter et al 2014;Dinsmore et al 2013) we found a mixture of controls on stream CO2 operating at different time-scales generating a highly dynamic stream CO2 pattern. These time-scales covers seasonal patterns to diel cycles, or even shorter scales associated to discharge events.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with findings from similar studies from other environments (arctic tundra, boreal forest, temperate peatlands, alpine) (e.g. Rocher-Ros et al 2019;Riml et al 2019;Crawford et al 2017;Peter et al 2014;Dinsmore et al 2013) we found a mixture of controls on stream CO2 operating at different time-scales generating a highly dynamic stream CO2 pattern. These time-scales covers seasonal patterns to diel cycles, or even shorter scales associated to discharge events.…”
Section: Discussionsupporting
confidence: 92%
“…Such diel CO2 patterns are commonly observed in stream CO2 time series at base-flow or during receding flow conditions (e.g. Riml et al 2019;Peter et al 2014) and are especially pronounced in amplitude in nutrient-rich streams or in streams without canopy shading (Alberts et al 2017;Crawford et al 2017;Rocher-Ros et al 2019). Initial evaluation of the δ 13 C-DIC data collected during the spring period suggests a relatively steady mixture of geogenic and biogenic DIC although somehow related to variations in discharge ( Figure 11).…”
Section: Discussionmentioning
confidence: 86%
“…If photo‐oxidation is the major driver, we predicted that CO 2 concentrations in streams would increase from night to day, when photo‐oxidation rates would be greatest (Cory et al 2014). By contrast, if GPP is the major driver, then CO 2 concentrations would decrease from night to day, when photosynthetic CO 2 fixation is greatest (Rocher‐Ros et al 2020).…”
Section: Figmentioning
confidence: 99%
“…Despite this similarity, estimates from stream network modelling were generally higher than for the mass balance. There are several possibilities for this difference; the mass balance does not take into account internal production of CO 2 throughout the stream network which has been observed by others (Hotchkiss et al, 2015;Hutchins et al, 2017;Rocher-Ros, Sponseller, Bergström, Myrstener, & Giesler, 2019) and may therefore underestimate emissions. Another possibility is the stream network emissions were overestimated since the gas exchange was modelled using relationships developed in Sweden (Natchimuthu et al, 2017), and may not reflect the conditions in the western Canadian Taiga.…”
Section: Estimates Of Fluvial Co 2 and Ch 4 Emissionsmentioning
confidence: 99%